Analysis of soluble proteins/aggregates derived from gluten-emulsifiers systems - Gómez, Analía Verónica (2012)
According to their amphiphilic nature, emulsifiers as Sodium Stearoyl Lactylate (SSL) and Diacetyl Tartaric Acid Esters of Monoglycerides (DATEM) favor interactions between dough components, although the mechanisms of action are not fully elucidated. There is quite information about the nature of emulsifier-gluten protein interaction and its consequence in breadmaking quality, but no reports were found about structural changes in gluten proteins produced by SSL and DATEM and their influence in aggregation-disaggregation gluten protein phenomena. For this reason the aim of this work was to investigate changes on gluten protein structure induced by SSL and DATEM; through the analysis of the nature of soluble aggregates by different SDS-PAGE techniques, and gliadins and glutenins extracted from gluten samples by RP-HPLC. At 1% level, SSL allowed the solubilization of a large proportion of high molecular mass aggregates, suggesting that at this high level, this emulsifier cause changes in native gluten protein network. Nevertheless, no significant differences in the protein quantity extracted of the distinct gliadins and glutenins were observed. On the other hand, the emulsifier SSL at 0.5% (w/w) level also allowed the extraction of a high percentage of γ-gliadins and low molecular weight glutenins in comparison with gluten and gluten-DATEM samples. In conclusion distinct quantity and quality of gliadins and glutenins were extracted from gluten samples, depending on the level and the chemical structure of each emulsifier.